The evolving science of detection of "blood doping" - Lundby, C.; Robach, P.; Saltin, B. (British Journal of Pharmacology, 2012)
Blood doping practices in sports have been around for at least half a century and will likely remain for several years to come. The main reason for the various forms of blood doping to be common is that they are easy to perform, and the effects on exercise performance are gigantic. Yet another reason for blood doping to be a popular illicit practice is that detection is difficult. For autologous blood transfusions, for example, no direct test exists, and the direct testing of misuse with recombinant human erythropoietin (rhEpo) has proven very difficult despite a test exists. Future blood doping practice will likely include the stabilization of the transcription factor hypoxia-inducible factor which leads to an increased endogenous erythropoietin synthesis. It seems unrealistic to develop specific test against such drugs (and the copies hereof originating from illegal laboratories). In an attempt to detect and limit blood doping, the World Anti-Doping Agency (WADA) has launched the Athlete Biological Passport where indirect markers for all types of blood doping are evaluated on an individual level. The approach seemed promising, but a recent publication demonstrates the system to be incapable of detecting even a single subject as `suspicious` while treated with rhEpo for 10-12 weeks. Sad to say, the hope that the 2012 London Olympics should be cleaner in regard to blood doping seems faint. We propose that WADA strengthens the quality and capacities of the National Anti-Doping Agencies and that they work more efficiently with the international sports federations in an attempt to limit blood doping.